Lineage-Restricted Regulation of SCD and Fatty Acid Saturation by MITF Controls Melanoma Phenotypic Plasticity - Vivas-García, Yurena; Falletta, Paola; Liebing, Jana; Louphrasitthiphol, Pakavarin; Feng, Yongmei; Chauhan, Jagat; Scott, David A; Glodde, Nicole; Chocarro-Calvo, Ana; Bonham, Sarah; Osterman, Andrei L; Fischer, Roman; et al. (Molecular cell, 2020)
Phenotypic and metabolic heterogeneity within tumors is a major barrier to effective cancer therapy. How metabolism is implicated in specific phenotypes and whether lineage-restricted mechanisms control key metabolic vulnerabilities remain poorly understood. In melanoma, downregulation of the lineage addiction oncogene microphthalmia-associated transcription factor (MITF) is a hallmark of the proliferative-to-invasive phenotype switch, although how MITF promotes proliferation and suppresses invasion is poorly defined. Here, we show that MITF is a lineage-restricted activator of the key lipogenic enzyme stearoyl-CoA desaturase (SCD) and that SCD is required for MITF melanoma cell proliferation. By contrast MITF cells are insensitive to SCD inhibition. Significantly, the MITF-SCD axis suppresses metastasis, inflammatory signaling, and an ATF4-mediated feedback loop that maintains de-differentiation. Our results reveal that MITF is a lineage-specific regulator of metabolic reprogramming, whereby fatty acid composition is a driver of melanoma phenotype switching, and highlight that cell phenotype dictates the response to drugs targeting lipid metabolism.